Design universal, acessibilidade e tecnologia assistiva : a formação profissional do terapeuta ocupacional na perspectiva da equidade - Marins, Simone Cristina Fanhani (2011)
The occupational therapist activity seeks to promote autonomy and independence for the general population in the different areas of personal and social interaction, participating in the development of social policies. Among the intervention strategies is the use of accessibility resources and technologies to enhance human functionality. The profession strives to guarantee peoples rights regardless of special needs, whether temporary or permanent. Professional legislation entitles the occupational therapist to the use of assistive technology in daily activities and in instrumental daily life activities. This research s objective was to analyze occupational therapist education in order to work with accessibility resources and assistive technology. It considered seventeen Brazilian bachelor courses, nine of which private, four federal, and four state schools, as well as forty junior and senior students. Data collection techniques included documental analysis and surveys. According to the used method, in the first step theoretical and practical subjects from the curriculum were considered. The second step used surveys to assess students perception of their own capability in the areas of accessibility and assistive technology. The results showed an overall average of 71,96 hours dedicated to assistive technology, representing 2,25% of the minimum required time, concentrated in subjects with minimum required times varying between 59 and 89 hours. The documental analysis results showed that these contents are presented in specific required subjects (82,4%) and in non-specific required subjects, where they are part of the curriculum (64,7%). A disparity between this research s findings and the students perception was observed. Students state that 42,5% of the contents were offered in specific subjects and in the subjects referred to as Applied . Some of the main results indicate that there is no identifiable systematization of contents and time spent and that the contents are treated superficially. Furthermore, they show that the students feel more prepared to evaluate than to use technological resources and do not feel ready to create and develop accessibility resources and assistive technology. The results obtained in this research can contribute to improve and better direct the course content in light of the development of accessibility resources and technologies within the parameters of inclusion and in doing so, to better qualify future professionals.